Limitations on the stocks portfolio optimization on the Banja Luka Stock Exchange - Горан Радивојац; Милош Грујић (Acta Economica, 2016)
The term „portfolio analysis”, which was introduced in the economic theory by Harry Markowitz, is not a new term in scientific literature. However, in the papers of local and foreign authors, analysis and criticism are mainly based on the examples of developed capital markets. There are very few cases of application of the portfolio analysis on domestic capital market. The focus of this paper is on implementation of diversification of the shares on the Banja Luka Stock Exchange. Using Markowitz’s portfolio selection, we will prove that diversification, including all limitations, is possible and applicable onto the domestic capital market.